1985
DOI: 10.1063/1.335897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of space angle on constriction resistance and contact resistance for a point contact

Abstract: It can generally be considered that an actual contact makes an angle with the extension of the contact surface because the tip of a contact element is convex in shape (macroscopically) and has surface roughness (microscopically). The effect of this angle on constriction resistance and contact resistance for a point contact is analyzed theoretically by solving Laplace’s equation subject to boundary conditions determined by a modeled morphology of the contact. The analysis leads to the modified formulas for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In the specific case of self-similar tips (Berkovich, cube-corner and conical geometries), simple geometrical considerations show that this resistance evolves as the reciprocal of the contact radius 𝑟 𝑐 (Eq. 6) (adapted from [50]).…”
Section: Importance Of Contact Area In Nanoindentation -Effect Of Mat...mentioning
confidence: 99%
“…In the specific case of self-similar tips (Berkovich, cube-corner and conical geometries), simple geometrical considerations show that this resistance evolves as the reciprocal of the contact radius 𝑟 𝑐 (Eq. 6) (adapted from [50]).…”
Section: Importance Of Contact Area In Nanoindentation -Effect Of Mat...mentioning
confidence: 99%
“…For the most real contact surfaces, the average space angle of asperities are generally less than 20° [13], this will result in an increase on the electrical resistance at most 4.6% only.…”
Section: ) Asperity Anglementioning
confidence: 99%
“…Furthermore, Sano [13,14] investigated the effect of the space angle on the constriction resistance. The space angle was defined as the angle made by the asymptote surface with the extension of the contact surface (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to achieve reliable junctions in nanodevices can be considered as obtaining lower metal-metal or metal-semiconductor contact resistance. It has been reported that the contributions to contact resistance include micro-scale geometry [1][2][3][4][5], oxide layer of semiconductor materials [6,7], difference of Fermi energy between nanomaterials and electrodes [8], and contact force between two metal films [3]. Furthermore, dependence on contact force [3,9] was investigated, as well as dependence on contact length [10], to understand characteristics of contact resistance.…”
Section: Introductionmentioning
confidence: 99%